Morphometric Assessment of the Mandible and Mandibular Foramen in the Pakistani Population - Hina, Mohtasham; Maryam, Areeba; Zahra, Dua; Dua Fatima; Sardar, Munazza; Rasheed, Ammara (Journal of Rawalpindi Medical College, 2025)
Objective: Mandibular size and foraminal anatomy vary from population to population because they provide passage to important anatomical structures that have great importance during clinical procedures. Through a comprehensive literature review, we found that no existing morphometric data are available for the Pakistani population. This cross-sectional analysis is performed on 86 dry adult mandibles (from Rawalpindi Medical University) to identify key mandibular dimensions and foraminal positions in a Pakistani sample. Methods: Each mandible was measured twice with digital Vernier calipers (0.01 mm precision). Paired (left vs. right) parameters included mandibular body length, ramus height, and distances from the mandibular foramen to the anterior and posterior borders of the ramus. Unpaired parameters (bicondylar width and bigonial width) were measured across specimens. Morphological variants (e.g., accessory mental foramina) were also observed. Statistical comparison of sides used paired two-tailed t-tests or Wilcoxon signed-rank tests (significance set at p<0.05). Results: Out of 100 mandibles examined, 86 were suitable for analysis. Significant side-to-side differences were found for mandibular body length, the distance from the anterior border to the mandibular foramen, and mandibular notch distance to angle (p<0.05). No accessory mental foramina were observed. Unpaired measurements such as bicondylar width (114.53 ± 5.44 mm), bigonial width (94.47 ± 6.93 mm), and symphysis menti height (28.57 ± 4.45 mm) were recorded. Conclusion: The findings offer population-specific morphometric data on the mandible and foramina in Pakistan and may serve as a reference for anatomical and clinical research. Keywords: Mandible; Mandibular Canal; Population; Anatomy, Cross-Sectional; Pakistan